Los caminos menos transitados La administración Arias Sánchez y la redefinición de la política exterior de Costa Rica, 20062010. - Stagno Ugarte, Bruno (Editorial Universidad Nacional (EUNA), 2013)
The roads less traveled relate the behind the scenes of some of the most important decisions and actions that redefined the foreign policy of Costa Rica, under the second administration of President Óscar Arias Sánchez (2006-2010). Additionally, this book includes a chapter that addresses relations with Nicaragua, our most uncomfortable neighbor.